"This is a mailbox, right?": Associations of play materials with siblings' and friends' shared meanings during pretend play. (March 2022) - Howe, Nina; Leach, Jamie; DeHart, Ganie
Play materials designed to enhance children's pretense were investigated; namely, how the specific characteristics of the play sets (thematically open-ended village set vs thematically closed-ended train set) influenced children's play communication regarding their co-construction of shared meanings. Participants included 44 7-year-old focal children playing with both play sets with an older or younger sibling and a same-age friend. Play set differentially impacted the type of shared meanings children co-constructed; specifically, the village set promoted more simple strategies (e.g. descriptions) and clarifications (e.g. questions), and the train set facilitated more prosocial behavior (e.g. helping), regardless of play partner. Friends were more likely to initiate play ideas and engage in disruptive behavior (e.g. control, aggression) with the train versus the village. The pattern of findings indicated that children's play communications may be associated with the specific type of props and that all materials designed for pretense do not enhance it in the same way.